APOLOGETIC EVANGELICAL CONTEXTUAL CHRISTOLOGY: A Pragmatic Approach in the Islamic Context - Aftab Yunis Hakim (QUAERENS: Journal of Theology and Christianity Studies, 2024)
The conflict over Jesus Christ, the ‘Son of God,’ is not new. Thousands of years ago, the disciples faced similar trials; however, the challenge to solve this tension was not based on debates or natural theology, but rather to show the works of Christ. The researcher has argued that various studies on Christology have already been done, however, the Pakistani perspective demands the fullness of Christ in a quite unique way to reimagine Him in the context of socio-economic, political, and religious challenges. On the one hand, though the traditional way of doing Christology highly emphasized the personhood of Christ explaining Him from the eschatological perspective (though it is important), however, on the other hand, it makes Christ a pacifist Jesus who has no concern for the current issues. As a result, this kind of Christological articulation does not explain Christ’s presence in our struggles today. This piece further demonstrated that the context is not above Christ in discovering who He is in the midst of such a grave situation, but rather contextual realities provide the Pakistani Punjabi Church an opportunity to demonstrate the works of Christ. Furthermore, this study also argued that the real struggle is not being a minority in this context, but rather being marginalized (economically, politically, and religiously) is the real challenge. This study further argued that the core issue is the ecclesiastical responsibility to overcome all the issues in this context. As a result, ‘Apologetic Evangelical Contextual Christology’ has proposed seeing Christ in all His fullness in the Islamic Context.